2007
DOI: 10.1074/jbc.m611294200
|View full text |Cite
|
Sign up to set email alerts
|

Highly Tolerated Amino Acid Substitutions Increase the Fidelity of Escherichia coli DNA Polymerase I

Abstract: Fidelity of DNA synthesis, catalyzed by DNA polymerases, is critical for the maintenance of the integrity of the genome. Mutant polymerases with elevated accuracy (antimutators) have been observed, but these mainly involve increased exonuclease proofreading or large decreases in polymerase activity. We have determined the tolerance of DNA polymerase for amino acid substitutions in the active site and in different segments of E. coli DNA polymerase I and have determined the effects of these substitutions on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 59 publications
9
50
1
Order By: Relevance
“…At the Arg 696 site alone, we identified 13 amino acids representing polar, nonpolar, charged, and hydrophobic residues that could substitute for alanine. This is in contrast to previous work on Escherichia coli Pol I and TaqDNA polymerase using random mutagenesis of the entire polymerase molecule which suggested that this position is very highly conserved (28,29). The previously described mutation, R689W, which was identified in the human colorectal cancer cell line, DLD-1, has been demonstrated to be a strong mutator that is non-viable in haploid yeast (23).…”
Section: Mutagenesis Of Yeast Pol ␦ Residues Argcontrasting
confidence: 87%
“…At the Arg 696 site alone, we identified 13 amino acids representing polar, nonpolar, charged, and hydrophobic residues that could substitute for alanine. This is in contrast to previous work on Escherichia coli Pol I and TaqDNA polymerase using random mutagenesis of the entire polymerase molecule which suggested that this position is very highly conserved (28,29). The previously described mutation, R689W, which was identified in the human colorectal cancer cell line, DLD-1, has been demonstrated to be a strong mutator that is non-viable in haploid yeast (23).…”
Section: Mutagenesis Of Yeast Pol ␦ Residues Argcontrasting
confidence: 87%
“…The presence of one mutation was found to significantly increase the chances of another mutation at a structurally-interacting site. In the case of ionic interactions, the increase was almost 4-fold (Loh et al, 2007b). This is strong evidence of a role of compensatory mutations in shaping protein evolution.…”
Section: A) High Prevalence Of Suppressor Mutationsmentioning
confidence: 76%
“…Studies of three different proteins established that approximately one-third of random mutations in proteins have severe deleterious effects to their function (>90% loss of activity). Two of these are monomers, human 3-methyladenine DNA glycosylase (AAG, 298 amino acids long) (Guo et al, 2004a), and the 430 amino acids of the E. coli Pol I Kleenow fragment (Loh et al, 2007b). The third one is the E. coli lac repressor, a tetramer of four 360 amino acid polypeptides.…”
Section: Most Missense Mutations Affect Protein Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have created a large collection of PolI mutants that exhibit either an elevated or a reduced in vivo mutation rate, with a representation of fidelities spanning six orders of magnitude (23)(24)(25)(26). Here we report on the use of these mutants in competition experiments to investigate the relationship between replication fidelity and evolutionary survival.…”
mentioning
confidence: 99%